The World Book Student Discovery Encyclopedia (Vol.7) : M - World Book, Inc. (Chicago World Book, 2004)
A general elementary encyclopedia with brief illustrated articles covering an alphabetical array of topics.
Include Illustrations (some color) and Color Maps
Keywords: Children's encyclopedias and dictionaries -- Science